Therapeutic modulation of protein RBM3 for ischemic stroke treatment - Ávila-Gómez, Paulo; Vieites-Prado, Alba; Correa-Paz, Clara; Del Pozo-Filíu, Lucía; Palomar-Alonso, Nuria; Campos, Francisco; López-Arias, Esteban (Frontiers in Pharmacology, 2025)
Several preclinical assays and clinical trials have found hypothermia as an efficient protective treatment for stroke. However, systemic hypothermia impairs several physiological functions being difficult to implement in acute critical patients. A deeper understanding of the mechanisms underlying the therapeutic effects of hypothermia could inspire new treatments based on the protective effects of cold. Furthermore, this could contribute to the reduction of the side effects associated with it. One of the metabolic landmarks of hypothermia is the overexpression of a small subset of shock proteins while global protein synthesis is reduced. Among these cold-shock proteins, RBM3 (RNA-binding motif protein 3) seems to play a central protective role. In physiological conditions, which is involved in the regulation of protein synthesis. In several models of cerebral diseases, in vitro and in vivo, RBM3 exhibited the ability to mitigate apoptosis or increase neural proliferation. In stroke models, RBM3 has shown specially promising effects attenuating neural damage and enhancing cell survival. Future prospects should be directed towards the design of efficient strategies to modulate RBM3 levels. This mini-review aims to summarize the progress made in understanding the role of RBM3 in cerebral tissue protection, while encouraging efforts to address research gaps, particularly in its modulation and clinical application.